Emotional Responses to Racial Violence: Analyzing Sentiments and Emotions Among Black Women in Missouri - Ivy Smith; Sheretta T. Butler-Barnes (Information, 2025)
This study examines the emotional responses of Black women in Missouri regarding incidents of racial violence in the United States. Grounded in an analysis of self-reported emotions, this study explores how Black women (n = 384, Mage = 37) express their emotional experiences in response to racial violence. Utilizing the Multiple Affect Adjective Checklist-Revised (MAACL-R), sentiment analysis was used to assess the overall emotional tone of participants’ responses, while emotion analysis was used to identify specific emotions expressed. The findings highlight the complexities of Black women’s emotional responses, considering factors such as coping mechanisms, racial identity beliefs, spirituality and religiosity, and resilience and strength. By applying computational methods to analyze these emotions, this study reveals how racial violence shapes sentiment and emotional expression patterns. Furthermore, it highlights the significance of acknowledging the complex ways Black women navigate and process racial violence.